Purification and Characterization of Catalaze Enzymes from Coriander (Coriandrum sativum) Leaves - DEMIR, HULYA; COBAN, ABDULKADIR; CIFTCI, MEHMET (Asian Journal of Chemistry, 2010)
Catalaze (H2O2:H2O2 oxidoreductase; E.C 1.11.1.6) was purified from Coriander (Coriandrum sativum) leaves. The kinetic behaviour and some properties of the enzyme were also investigated. The purification was done at 4 ºC in two steps: (a) ammonium sulfate fractionation and (b) DEAE-Sephadex A50 ion exchange chomatography. The enzyme was obtained with a yield of 10.67 % and had a specific activity of 89.68 EU/mg protein. Optimum pH, stable pH, optimum temperature, molecular weight, KM and Vmax values for H2O2 was also determined. The overall purification was about 64.06-fold. SDS-PAGE of the purified enzyme showed a single band. Enzymatic activity was spectrophotometrically measured at 240 nm. The molecular mass was estimated to be 60.95 kDa by SDS-PAGE and 58.12 kDa by Sephadex G-150 gel filtration column chromatography. The enzyme had optimum pH at 7.3 and was stable at pH 7.3 in 0.1 M tris-HCl buffer. The optimum temperature was at 30 ºC. The KM value for H2O2 was 7.87 mM. The Vmax value for this substrate was 42.19 EU/mL.